2015
DOI: 10.1145/2738036
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Supporting Cross-Device Web Search for Exploratory Tasks with Mobile Touch Interactions

Abstract: Mobile devices enable people to look for information at the moment when their information needs are triggered. While experiencing complex information needs that require multiple search sessions, users may utilize desktop computers to fulfill information needs started on mobile devices. Under the context of mobileto-desktop web search, this article analyzes users' behavioral patterns and compares them to the patterns in desktop-to-desktop web search. Then, we examine several approaches of using Mobile Touch Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…These approaches require acquiring user information which may be hard to obtain. Other information such as users' MTI behaviors can also help to identify a fine-grained user interest, and thus can be used to filter out the noise [10]. In this paper, we try to combine the advantages of social navigation and MTIs, and expect further improvement on search performance.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…These approaches require acquiring user information which may be hard to obtain. Other information such as users' MTI behaviors can also help to identify a fine-grained user interest, and thus can be used to filter out the noise [10]. In this paper, we try to combine the advantages of social navigation and MTIs, and expect further improvement on search performance.…”
Section: Related Workmentioning
confidence: 99%
“…Including additional information increases the risk of having noise. Previous studies found that applying subdocument relevant information can help to reduce noise [4,10]. Such information can be inferred either from gaze attention [4] or from mobile touch interactions (MTI) [10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations